In vitro and in vivo roles of sphingosine kinase 2 during dengue virus infection. (14th March 2019) - Al-Shujairi, Wisam H.; Clarke, Jennifer N.; Davies, Lorena T.; Pitman, Melissa R.; Calvert, Julie K.; Aloia, Amanda L.; Pitson, Stuart M.; Carr, Jillian M.
Abstract : There is growing evidence of the influence of sphingosine kinase (SK) enzymes on viral infection. Here, the role of sphingosine kinase 2 (SK2), an isoform of SK prominent in the brain, was defined during dengue virus (DENV) infection. Chemical inhibition of SK2 activity using two different SK2 inhibitors, ABC294640 and K145, had no effect on DENV infection in human cells in vitro . In contrast, DENV infection was restricted in SK2 −/− immortalized mouse embryonic fibroblasts (iMEFs) with reduced induction of IFN-β mRNA and protein, and mRNA for the IFN-stimulated genes (ISGs) viperin, IFIT1, IRF7 and CXCL10 in DENV-infected SK2 −/− compared to WT iMEFs. Intracranial (ic) DENV injection in C57BL/6 SK2 −/− mice induced body weight loss earlier than in WT mice but DENV RNA levels were comparable in the brain. Neither SK1 mRNA or sphingosine-1-phosphate (S1P) levels were altered following ic DENV infection in WT or SK2 −/− mice but brain S1P levels were reduced in all SK2 −/− mice, independent of DENV infection. CD8 mRNA was induced in the brains of both DENV-infected WT and SK2 −/− mice, suggesting normal CD8+ T-cell infiltration into the DENV-infected brain independent of SK2 or S1P. Thus, although SK2 may be important for replication of some viruses SK2 activity does not affect DENV infection in vitro and SK2 or S1P levels do not influence DENV infection or T-cell infiltration in the context of infection in the brain.